Cost Overrun in Construction Projects in Malaysia: A Study on Contractor Related Factors - Norul Izzati, M. Ashaari; Mohd Amir Shazwan, Hashim; Yong, Sheve Huey (INTI International University, 2019)
In construction industry, the key to a successful project lies on the quality of works, completed within the stipulated time with the planned budget. However, unexpected situations from different parties involved may lead to the delay of the works that eventually affect the whole cost of the project. The contractor is always been the main party who is dealing with the actual construction scenario that may affect the overall process of the construction project. Hence, this paper aim to investigate the contractor related factors that lead to cost overrun in the Malaysian construction project in Malaysia. A quantitative method was employed in this research by obtaining the data from questionnaire survey to G7 contractors in Selangor. The data were analysed using statistic method and Relative Importance Index (RII) method. The results indicate that improper planning and poor site management ranked the main factors that affect the cost overrun in construction project. Therefore, the results of this study will be beneficial to the contractors in achieving effective cost performance in construction projects in Malaysia.